INTRACRANIAL ARTERIAL LOOP WITH A COMPLEX PARTIALLY THROMBOSED LARGE ANEURYSM ON THE POSTERIOR CIRCULATION: WHAT TO DO NEXT? - Julia-Melinda Domahidi; George-Mihai Cosma; Rafael-Florin Chis; Ioan Stefan Florian (Romanian Neurosurgery, 2024)
Introduction